2024
DOI: 10.1039/d3ta07462e
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acid additive with a double regulating mechanism for high-performance aqueous zinc ion batteries

Hongzhi Wang,
Huanhuan Wang,
Weiguo Zhang
et al.

Abstract: Aqueous zinc ion batteries (AZIBs) are considered as future energy storage devices because of their high safety, low cost, and environmental friendliness. However, the growth of dendrites and side reactions...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…The Zn//MnO 2 full cells are appealing compared to previous reports, as shown in Figure S10 and summarized in Table S2. , MBA additives also contribute to an enhanced self-discharge performance via inhibiting the parasitic reactions. As shown in Figure d,e, after resting for 48 h, Zn//MnO 2 full cells retain 99.2% of the original capacity in Zn 1 N 20 electrolyte, which is much better than the cells in Zn 1 electrolytes (84.1%).…”
Section: Results and Discussionmentioning
confidence: 86%
“…The Zn//MnO 2 full cells are appealing compared to previous reports, as shown in Figure S10 and summarized in Table S2. , MBA additives also contribute to an enhanced self-discharge performance via inhibiting the parasitic reactions. As shown in Figure d,e, after resting for 48 h, Zn//MnO 2 full cells retain 99.2% of the original capacity in Zn 1 N 20 electrolyte, which is much better than the cells in Zn 1 electrolytes (84.1%).…”
Section: Results and Discussionmentioning
confidence: 86%
“…In addition to the abovementioned polymeric materials, the application of organic small molecules has emerged as another effective approach for enhancing the electrochemical properties of the SEI layer. These organic small molecules, such as amino acids 118–122 and organic acids, 123 also provide high tunability in terms of chemical structure and functionality. In recent studies, amino acids have been shown to generally exhibit a high durability under harsh cycling conditions.…”
Section: Organic Materials For Interfacial Layersmentioning
confidence: 99%